The structure of t-butyl 7-[2-(4-fluorophenyl)-3-phenyl-4-(phenylcarbamoyl)-5-(propan-2-yl)-1H-pyrrol-1-yl]-3,5-dihydroxyheptanoate, C37H43FN2O5 - Sun Wei-Jie; Wang Zhi-Chao; Jiang Cheng-Jun (Zeitschrift für Kristallographie - New Crystal Structures)
C37H43FN2O5, monoclinic, P21 (no. 4), a = 13.8818(6) Å, b = 8.7373(4) Å, c = 15.6295(7) Å, β = 113.356(2)°, V = 1740.36(14) Å3, Z = 2, Rgt (F) = 0.0527, wRref (F 2) = 0.1346, T = 170 K.